121k views
1 vote
Lim x-π/4 x(cos³x-sin³x)/(tan4xcosx)

User Notlkk
by
5.9k points

1 Answer

3 votes

For starters, we can write


\cos^3x-\sin^3x=(\cos x-\sin x)(\cos^2x+\cos x\sin x+\sin^2x)=(\cos x-\sin x)(1+\cos x\sin x)

Then we can absorb the factor of
\cos x from the denominator into the numerator:


(x(\cos^3x-\sin^3x))/(\tan4x\cos x)=(x(1-\tan x)(1+\cos x\sin x))/(\tan 4x)

Then provided that


\displaystyle\lim_(x\to\pi/4)(1-\tan x)/(\tan4x)

exists, we can split the limit of the product into the product of limits:


\displaystyle\lim_(x\to\pi/4)(x(\cos^3x-\sin^3x))/(\tan4x\cos x)=\left(\lim_(x\to\pi4)x(1+\cos x\sin x)\right)\left(\lim_(x\to\pi4)(1-\tan x)/(\tan 4x)\right)


x(1+\cos x\sin x) is continuous at
x=\frac\pi4, so that limit reduces to
\frac\pi4\left(1+\cos\frac\pi4\sin\frac\pi4\right)=\frac{3\pi}8.

The remaining limit is of indeterminate form 0/0; one application of L'Hopital's rule shows that the limit would be


\displaystyle\lim_(x\to\pi/4)(1-\tan x)/(\tan4x)=\lim_(x\to\pi/4)(-\sec^2x)/(4\sec^24x)=-\frac12

so the final limit would be
-(3\pi)/(16).

But if you haven't learned about L'Hopital's rule (or if you're like me and prefer doing more work for some reason), we have to try something else: more trig identities!

Euler's formula and DeMoivre's theorem are very useful here:


e^(ix)=\cos x+i\sin x (Euler)


(\cos x+i\sin x)^n=\left(e^(ix)\right)^n=e^(inx) (DeMoivre)

Take
n=4; then


e^(4ix)=\cos4x+i\sin4x=(\cos^4x-6\cos^2x\sin^2x+\sin^4x)+i(4\cos^3x\sin x-4\cos x\sin^3x)


\implies\begin{cases}\cos4x=\cos^4x-6\cos^2x\sin^2x+\sin^4x\\\sin4x=4\cos^3x\sin x-4\cos x\sin^3x\end{cases}

So we have


\tan 4x=(4\cos^3x\sin x-4\cos x\sin^3x)/(\cos^4x-6\cos^2x\sin^2x+\sin^4x)

On the right side, divide through the numerator and denominator by
\cos^4x; doing so yields


\tan 4x=(4(\sin x)/(\cos x)-4(\sin^3x)/(\cos^3x))/(1-6(\sin^2x)/(\cos^2x)+(\sin^4x)/(\cos^4x))


\implies\tan4x=(4\tan x-4\tan^3x)/(1-6\tan^2x+\tan^4x)=(4\tan x(1-\tan x)(1+\tan x))/(1-6\tan^2x+\tan^4x)

So in the limit, we can simplify the rational expression even further:


\displaystyle\lim_(x\to\pi/4)(1-\tan x)/(\tan4x)=\lim_(x\to\pi/4)(1-\tan x)/((4\tan x(1-\tan x)(1+\tan x))/(1-6\tan^2x+\tan^4x))=\lim_(x\to\pi/4)(1-6\tan^2x+\tan^4x)/(4\tan x(1+\tan x))

and this function happens to be continuous at
x=\frac\pi4, so we can evaluate directly:


\displaystyle\lim_(x\to\pi/4)(1-\tan x)/(\tan4x)=(1-6\tan^2\frac\pi4+\tan^4\frac\pi4)/(4\tan\frac\pi4\left(1+\tan\frac\pi4\right))=-\frac48=-\frac12

We end up with the same limit we found earlier,
-(3\pi)/(16).

User RZet
by
6.5k points